PENGARUH MANAJEMEN PEMBELAJARAN TERHADAP KINERJA GURU DALAM MEWUJUDKAN PRESTASI BELAJAR SISWA - Wartomo Wartomo (HIBRUL ULAMA, 2025)
The purpose of this study was to examine the impact of student learning management at SMP PGRI Bantul on teacher performance in realizing student learning achievement. The research methodology used is a descriptive research model with survey techniques. The location of the research was at SMP PGRI Bantul with a total of 50 teachers as research subjects. The results of the study showed that learning management at SMP PGRI Bantul had a positive and significant effect on teacher performance in realizing student learning achievement. On the other hand, the results of the study can be concluded that student learning achievement is realized well, namely with the implementation of optimal teacher performance and learning management that is implemented effectively and efficiently.